Estrategias didácticas para la animación interactiva a la lectura del área de lengua y literatura en niños de tercer año de educación básica paralelo “B” en la unidad educativa “Luis Aurelio González” del cantón Guaranda, provincia Bolívar periodo 2023-2024 - Chacha Chimbo, Carlos Daniel (2024)
The present research project was carried out on the topic of didactic strategies for the interactive animation of reading in the area of language and literature in children in the third year of parallel "b" basic education. The approach of our research is mixed since we worked with 29 children and a sample, the approach of our research is descriptive, we used qualitative and quantitative methods, and for the collection of information we applied an interview guide and an observation sheet; through the interview guide based on a set of questions regarding the two variables we were able to obtain answers, the structured observation sheet; through the instrument that is the questionnaire, which helped us to determine if the proposed activities were fulfilled effectively. We realized that in the Educational Unit "Luis Aurelio Gonzales" they do not have clear didactic strategies for the interactive animation of reading, where it was determined that the children do not know their lateral dominance, which brings problems, since they will not have adequate skills that are indispensable in everyday life. In the scientific theory, didactic strategies for the interactive animation of reading were presented, since this will help to develop spatial and linguistic skills, which in turn contributes to the integral development of children and their ability to understand and communicate. The teacher has not developed mastery in the implementation of didactic strategies for interactive animation in children, which results in an insufficient reading experience, for which the use of interactive animation techniques was proposed to enrich the teaching- learning process, therefore, it was proposed the realization of an activity guide that will serve as a tool for the teacher